2018
DOI: 10.1101/cshperspect.a032078
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Single mRNA Translation Kinetics in Living Cells

Abstract: One of the last hurdles to quantifying the full central dogma of molecular biology in living cells with single-molecule resolution has been the imaging of single messenger RNA (mRNA) translation. Here we describe how recent advances in protein tagging and imaging technologies are being used to precisely visualize and quantify the synthesis of nascent polypeptide chains from single mRNA in living cells. We focus on recent applications of repeat-epitope tags and describe how they enable quantification of single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 79 publications
(171 reference statements)
5
43
0
Order By: Relevance
“…A multi-frame tag to monitor single RNA translation in two reading frames simultaneously We created a multi-frame (MF) tag to monitor, in living cells, the translation of single RNAs with overlapping open reading frames (ORFs). The tag builds off earlier technology to visualize translation using repeat FLAG or SunTag epitopes labeled by fluorescent Fab or scFv, respectively (Lyon and Stasevich, 2017;Morisaki and Stasevich, 2018). In the MF tag, FLAG epitopes in the 0 frame are separated from one another by SunTag epitopes in the -1 frame.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-frame tag to monitor single RNA translation in two reading frames simultaneously We created a multi-frame (MF) tag to monitor, in living cells, the translation of single RNAs with overlapping open reading frames (ORFs). The tag builds off earlier technology to visualize translation using repeat FLAG or SunTag epitopes labeled by fluorescent Fab or scFv, respectively (Lyon and Stasevich, 2017;Morisaki and Stasevich, 2018). In the MF tag, FLAG epitopes in the 0 frame are separated from one another by SunTag epitopes in the -1 frame.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of signal from the control translation site was fit to a single exponential decay and this decay was divided out from the FRAP recovery curves of the intentionally photobleached translation sites. The FRAP recovery curve can be thought of as the inverse of the harringtonine runoff curve (Morisaki and Stasevich, 2018). In this way, the FRAP recovery curve was fit to determine the average translation elongation rate (Fig.…”
Section: Ribosome Run-off Experiments and Fitsmentioning
confidence: 99%
“…While incredibly powerful, GFP-tagging has several limitations that have made it difficult to image the full lifecycles of proteins. First, long fluorophore maturation times prevent co-translational imaging of GFP-tagged nascent peptide chains 3,4 . By the time the GFP tag folds, matures and lights up, translation of the nascent peptide chain is long over.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging translation in living cells at single-molecule resolution is a new experimental 506 technology that has been applied to only a few genes so far [6-10, 14, 15], but the 507 number of such studies is expected to grow considerably in the near future [12]. transcription dynamics for a multi-state promoter.…”
mentioning
confidence: 99%
“…With the full and reduced models in hand, it becomes possible to predict how well 538 three modern methodologies would estimate elongation rates from single-molecule 539 measurements: Fluorescence Correlation Spectroscopy (FCS) [12], Fluorescence 540 Recovery After Photobleaching (FRAP) [8,9,12], and Run-Off Assays (ROA) after 541 perturbation with inhibitory drugs [7,10]. Through simulations on 2,647 genes, we 542 demonstrated that estimating elongation rates for long genes (>1000 codons) could be 543 achieved with great accuracy using any of these methodologies, provided that a minimal 544 number of mRNA spots are considered and with an appropriate temporal resolution as 545 demonstrated in Fig 3. However, our results suggest that FCS would be the most likely 546 method to provide an accurate elongation rate estimate (Fig 3A), especially for small 547 and medium size genes.…”
mentioning
confidence: 99%